PENGARUH PENGGUNAAN MEDIA DIGITAL SPINNING WHEEL TERHADAP KEAKTIFAN BELAJAR IPAS SISWA KELAS VI SD INPRES 6/75 CORAWALI KABUPATEN BONE - Mujahidah Mujahidah; Muhammad Ikhsan Sukaria; Nur Aeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is a quantitative research employing a pre-experimental design. It aims to determine the difference in students’ learning activeness in IPAS before and after the use of digital Spinning Wheel media, as well as to examine the effect of its implementation. The population of this study consisted of all sixth-grade students of SD Inpres 6/75 Corawali, totaling 20 students. The sampling technique used was saturated sampling. Data were collected using a questionnaire administered before and after the treatment. The data analysis techniques included descriptive and inferential statistics using the Paired Sample t-Test. The results showed that students’ learning activeness in IPAS before the use of the digital Spinning Wheel media was in the low category with a mean score of 58.45, while after the implementation it increased to 70.05 in the good category. The study concludes that there is a significant effect of the use of digital Spinning Wheel media on students’ learning activeness in IPAS at SD Inpres 6/75 Corawali, as evidenced by a significance value of 0.001 < 0.05